Advantages and Disadvantages of Applying the NHT Type Cooperative Learning Model Physics Learning in School - Hadma Yuliani; Normilawati Normilawati; Tiya Andani; Maryam Aulia (Universitas Lambung Mangkurat, 2021)
This study analyses the advantages and disadvantages of cooperative learning type Numbered Head Together (NHT). The method in this research is a literature study based on previous research. The analysis technique used in this research is descriptive qualitative obtained from books and journals. Based on literature from 26 articles in scientific journals, it was found that the advantages of this type of NHT cooperative learning model are to make students more active, make students more interested in learning, think critically and responsibly and can improve student learning outcomes. While the obstacle in this learning model is the lack of time management) so that not all students can present the results of the discussions obtained during the learning process